Probing the chemistry, electronic structure and redox energetics in pentavalent organometallic actinide complexes - Graves, Christopher R; Vaughn, Anthony E; Morris, David E; Kiplinger, Jaqueline L (Inorganic chemistry, 2008)
Complexes of the early actinides (Th-Pu) have gained considerable prominence in organometallic chemistry as they have been shown to undergo chemistries not observed with their transition- or lanthanide metal counterparts. Further, while bonding in f-element complexes has historically been considered to be ionic, the issue of covalence remains a subject of debate in the area of actinide science, and studies aimed at elucidating key bonding interactions with 5f-orbitals continue to garner attention. Towards this end, our interests have focused on the role that metal oxidation state plays in the structure, reactivity and spectral properties of organouranium complexes. We report our progress in the synthesis of substituted Usup V-imido complexes using various routes: (1) Direct oxidation of Usup IV-imido complexes with copper(I) salts; (2) Salt metathesis with Usup V-imido halides; (3) Protonolysis and insertion of an Usup V-imido alkyl or aryl complex with H-N{double_bond}CPhsub 2 or N{triple_bond}C-Ph, respectively, to form a Usup V-imido ketimide complex. Further, we report and compare the crystallographic, electrochemical, spectroscopic and magnetic characterization of the pentavalent uranium (Csub 5Mesub 5)sub 2U({double_bond}N-Ar)(Y) series (Y = OTf, SPh, C{triple_bond}C-Ph, NPhsub 2, OPh, N{double_bond}CPhsub 2) to further interrogate the molecular, electronic, and magnetic structures of this new class of uranium complexes.